The Use of Directing Technologies in the System of Additional Education - Grigorieva, Elena Ivanovna; Kruglova, Marina Gennadievna; Asatryan, Olga Fyodorovna; Oparina, Nina Alexandrovna; Gribkova, Galina Ivanovna; Yushchenko, Natalia Sergeevna (Edelweiss Applied Science and Technology, 2021)
The study deploys various research methods. The theoretical methods include analysis, summarization, comparison, synthesis, and systematization of scientific and educational methodical literature to determine the current state of the problem under study. The empirical methods comprise purposeful observation, conversations, interviewing, questionnaire, and testing. In addition, a pedagogical experiment is conducted to test the experimental methods of using directing technologies in organizing the musical-pedagogical process in additional education institutions. Statistical methods are used in quantitative and qualitative processing of the study results, the objectivity of the results is tested using Pearson’s consistency criterion χ2.The need for the formation of a directing space of musical pedagogy as an important condition for improving the professional mastery of teachers in additional education is substantiated. The major directions for the implementation of directing technologies for the development of specialists’ competencies are revealed. The directing space created in the process of lessons and the demonstration of students’ achievements in performance contributes to students’ musical, aesthetic and spiritual, and moral development, the improvement of their performance skills, and the development of motivation for educational and creative and performance activity.